2008
DOI: 10.1242/jcs.034082
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the ATP-gated P2X7 receptor promotes axonal growth and branching in cultured hippocampal neurons

Abstract: During the establishment of neural circuits, the axons of neurons grow towards their target regions in response to both positive and negative stimuli. Because recent reports show that Ca2+ transients in growth cones negatively regulate axonal growth, we studied how ionotropic ATP receptors (P2X) might participate in this process. Our results show that exposing cultured hippocampal neurons to ATP induces Ca2+ transients in the distal domain of the axon and the concomitant inhibition of axonal growth. This effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
105
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 58 publications
13
105
0
Order By: Relevance
“…Taken together with our previous findings, our results indicate that activation of P2Y1 potentiates the PI3K-Akt-GSK3 pathway to promote axon elongation, whereas ATP exerts an opposing effect, downregulating the signaling through this pathway and inhibiting axon growth. ADP activation of P2Y1 increases Akt and GSK3 phosphorylation while promoting axon elongation, an effect previously demonstrated following P2X7 inhibition (Diaz-Hernandez et al, 2008). This enhanced elongation can be impaired by inhibiting PI3K, whereas the attenuation of axon growth by P2Y1 inhibition can be counteracted by inhibiting GSK3, and such inhibition has been previously shown to induce axonal elongation (Garrido et al, 2007).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Taken together with our previous findings, our results indicate that activation of P2Y1 potentiates the PI3K-Akt-GSK3 pathway to promote axon elongation, whereas ATP exerts an opposing effect, downregulating the signaling through this pathway and inhibiting axon growth. ADP activation of P2Y1 increases Akt and GSK3 phosphorylation while promoting axon elongation, an effect previously demonstrated following P2X7 inhibition (Diaz-Hernandez et al, 2008). This enhanced elongation can be impaired by inhibiting PI3K, whereas the attenuation of axon growth by P2Y1 inhibition can be counteracted by inhibiting GSK3, and such inhibition has been previously shown to induce axonal elongation (Garrido et al, 2007).…”
Section: Discussionmentioning
confidence: 78%
“…However, their role in the development of neuronal morphology and axon growth remains largely unknown. We previously demonstrated that ATP, acting at the purinergic P2X7 receptor, negatively modulates axon growth, generating an increase in calcium at the distal axon (Diaz-Hernandez et al, 2008), whereas inhibition or suppression of this receptor promotes axon elongation. The present study demonstrates that ADP enhances axon growth in cultured hippocampal neurons through the activation of the metabotropic P2Y1 receptor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both P2X3 and P2X7 receptors were shown to inhibit axonal growth and branching of developing motor axons [19], cultured hippocampal neurons [21], and neuroblastoma cells [22]. Moreover, activation of P2X7 receptors was shown to promote the survival of cerebellar granule cells [23,24], but the death of cultured striatum-derived neural progenitors [25], a conflicting observation that now can be explained by the recent detection and characterization of P2X7 receptor splice variants with distinct functional properties [26,27].…”
Section: Introductionmentioning
confidence: 99%